2018
DOI: 10.1186/s12885-018-4391-9
|View full text |Cite
|
Sign up to set email alerts
|

PEST-containing nuclear protein mediates the proliferation, migration, and invasion of human neuroblastoma cells through MAPK and PI3K/AKT/mTOR signaling pathways

Abstract: BackgroundPEST-containing nuclear protein (PCNP), a novel nuclear protein, is involved in cell proliferation and tumorigenesis. However, the precise mechanism of action of PCNP in the process of tumor growth has not yet been fully elucidated.MethodsShRNA knockdown and overexpression of PCNP were performed in human neuroblastoma cells. Tumorigenic and metastatic effects of PCNP were examined by tumor growth, migration, and invasion assays in vitro, as well as xenograft tumor assay in vivo.ResultsPCNP over-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 56 publications
1
64
0
Order By: Relevance
“…Animal experiments were approved by the Committee of Medical Ethics and Welfare for Experimental Animals of Henan University School of Medicine (HUSOM-2017-207) in compliance with the Experimental Animal Regulations formulated by the National Science and Technology Commission, China. Animal studies were performed as previously described with slight modifications [26]. Thirty-six BALB/C nude mice (4-week-old, male) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Certificate No.…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments were approved by the Committee of Medical Ethics and Welfare for Experimental Animals of Henan University School of Medicine (HUSOM-2017-207) in compliance with the Experimental Animal Regulations formulated by the National Science and Technology Commission, China. Animal studies were performed as previously described with slight modifications [26]. Thirty-six BALB/C nude mice (4-week-old, male) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Certificate No.…”
Section: Methodsmentioning
confidence: 99%
“…The expression level of Ki67 is closely associated with the proliferation, invasiveness, and clinical outcome of a number of malignant tumours . Ki67 is regarded as an important proliferative marker and has been widely adopted in determining the proliferation of cancer cells . In line with the in vitro findings, the results showed that the expression of Ki67 was decreased in the TIPE2 group and increased in the sh‐TIPE2 group.…”
Section: Discussionmentioning
confidence: 59%
“…There are two major pathways leading to apoptosis in the mammalian system: an intrinsic pathway that occurs through the mitochondria and an extrinsic pathway initiated by death receptors . Caspases can be activated in response to diverse apoptotic stimuli and PARP is further cleaved by activated caspase‐3, thus leading to the occurrence of apoptotic cascade . It has been reported that the adenovirus expressing human TIPE2 could obviously up‐regulate the expression levels of Bcl‐2‐associated X protein, cleaved caspase‐3, 9, and PARP in AGS human gastric cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…As a downstream effector of PI3K, Akt is a critical tumor factor ( 46 ). Activated Akt may regulate specific families of proteins (including the Bcl-2 family, caspase family and IKK family) associated with apoptosis and participate in the regulation of biological behavior of tumor cells ( 47 49 ). Previous studies have demonstrated that apoptosis is induced in gastric cancer cells via the PI3K/Akt pathway ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%